Buddhism and transgression : the appropriation of Buddhism in the contemporary West - Konik, Adrian. (Numen Book Series, 2009)
If Buddhism is to remain relevant to the contemporary era, through providing effective solutions to the proliferating and protean discursive problems encountered by its present-day practitioners, it cannot continue to ignore the role of discourse in the formation of subjectivity. In the interest of problematizing such 'ignorance,' this book explores the potential interface between Foucaultian discourse analysis and the development of an indigenous rationale for the practice of contemporary Western Buddhism, along with the growing significance of such a rationale for 'traditional' Buddhism in an era dominated by disciplinary/bio-power. Through doing so, this book radically re-conceptualizes the role of Buddhism in the world today by linking Buddhist practice with acts of discursive transgression.